Inclusion in Kindergarten, with An Aspect on Social Disadvantage - Stárek, Lukáš; Buchtová, Eliška (Studia Edukacyjne, 2020)
Social disadvantage is a construct that captures various dimensions of social position, such as economic status, educational attainment, as well as ethnicity. There is considerable evidence that social disadvantage is associated with emotional and behavioural problems in children (Bergin & Bergin, 2015). Nowadays, the theme of inclusion is accurate hence the issue of social disadvantages is not topic just for the pedagogy and pedagogical workers. At the same level, the authors focus on social disadvantages children in kindergartens. A challenge for intervention includes that social disadvantage is often structural in nature and, as a result, is largely impervious to change. It has been found that much of the association of low family income with adverse child development is indirect, through more proximal processes such as parental mental health and the home environment, rather than direct. Therefore, it is crucial for pedagogical workers such as teacher, teacher assistants etc., to acknowledge the sensitivity of social disadvantages which a family can face to. This chapter aims to highlights the issue of social disadvantages which can occur in kindergarten, with an emphasis on inclusion. By using the case studies the authors have found out how a status of a social disadvantage child influence a child and its family. Also, how this problematic is seen by pedagogical workers in chosen kindergarten.